Perang Tanding Sebagai Penentu Hak Milik Tanah Di Adonara - Eugenius Darwianto Sardita Putra; Yohanes Pedro Haju Leton; Stefanus Don Rade (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Engaging in warfare that encompasses cultural intricacies is far more deadly due to its repetitive nature and glorified heritage. Similar sentiments also apply to duels in the Adonara-East Flores-East Nusa Tenggara islands which are even more severe and magnificent because they are also considered heritage. Adonara is a small island with a long history of war crimes. Island communities generally consider conflict as a way to resolve problems, especially those related to women's issues and territorial/land disputes.